2019
DOI: 10.7554/elife.46630
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between serum amyloid A and secretory phospholipase A2

Abstract: Serum amyloid A (SAA) is an evolutionally conserved enigmatic biomarker of inflammation. In acute inflammation, SAA plasma levels increase ~1,000 fold, suggesting that this protein family has a vital beneficial role. SAA increases simultaneously with secretory phospholipase A2 (sPLA2), compelling us to determine how SAA influences sPLA2 hydrolysis of lipoproteins. SAA solubilized phospholipid bilayers to form lipoproteins that provided substrates for sPLA2. Moreover, SAA sequestered free fatty acids and lysoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…The SAA fold has been highly evolutionarily conserved since the Cambrian period, long before the emergence of HDL, suggesting that the primordial role of SAA does not involve HDL binding. Rather, it probably involves sequestration and transport of lipids, such as cell membrane debris, to avoid lipotoxicity at the sites of injury and facilitate tissue healing [ 78 •]. If verified in vivo, this role explains how the rapid and massive generation of SAA hours after the onset of acute injury, infection, or inflammation has benefitted the host survival throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SAA fold has been highly evolutionarily conserved since the Cambrian period, long before the emergence of HDL, suggesting that the primordial role of SAA does not involve HDL binding. Rather, it probably involves sequestration and transport of lipids, such as cell membrane debris, to avoid lipotoxicity at the sites of injury and facilitate tissue healing [ 78 •]. If verified in vivo, this role explains how the rapid and massive generation of SAA hours after the onset of acute injury, infection, or inflammation has benefitted the host survival throughout evolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, the levels of albumin, which normally sequesters most circulating NEFA and lyso-phospholipids, decrease in acute inflammation. Moreover, albumin’s affinity for NEFA decreases at acidic pH at the inflammation sites ([ 78 •] and references therein), causing potential accumulation of toxic lipids. Can SAA compensate for albumin deficiency and protect the inflammation sites from lipotoxicity?…”
Section: Saa Acts As a Detergent And A Lipid Scavengermentioning
confidence: 99%
See 1 more Smart Citation
“…Almost simultaneously, Cheng et al showed that recombinant SAA1 is able to bind LPS in a dose-dependent manner, diminishing LPS-induced proinflammatory effects [35]. In fact, SAA1 was shown to bind a variety of ligands, including lysophospholipids [49,50], HDL and other lipoproteins [51,52], cholesterol [53] and retinol [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SAA was shown to promote chronic inflammation in sarcoid granulomas via TLR2 signaling and activation of NF-κB, as well as cytokine production (224). Contrastingly, recent evidence suggests that during inflammation, SAA acts synergistically with secretory phospholipase-A to remove cell membrane debris, which suggests a partial involvement in anti-inflammatory repair processes (225). Interestingly, SAA has also been suggested to be responsible for the low HDL cholesterol and apoA1 levels observed in patients with active sarcoidosis (226, 227), which has been linked to an increased risk of atherosclerosis in sarcoidosis patients (219).…”
Section: Sarcoidosis: a Disease Lacking An Immunometabolic Switch?mentioning
confidence: 99%